2006
DOI: 10.1108/14684520610686292
|View full text |Cite
|
Sign up to set email alerts
|

Digital libraries: what do users want?

Abstract: Purpose-The purpose of this study was to determine user suggestions for Digital Libraries' functionality and features. Design/methodology/approach-A survey was conducted as part of this study, in which users' suggestions for Digital Libraries were solicited, as well as their ranking opinions on a range of suggested Digital Library features. Findings-The study revealed that, regardless of users' Information Technology (IT) backgrounds, their expectations of Digital Libraries' functionality are the same. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 17 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…Special emphasis is paid to task-based search, information retrieval, query processing and expansion, evaluation of returns' relevance, used information in a knowledge base, e-literacy and search skills, and sharing research information over the web (e.g. Arndt, 2010;Dickinson and Kim, 2002;Kani-Zabihi et al, 2006;Pomerantz et al, 2004;Spink, 2002;Vakkari, 2003). (4) The interoperability of the digital and networked libraries with the new paradigms of e-Science and e-learning has initiated a series of investigations on EL 30,6 the capability of the academic library to keep pace, and the librarians to engage with these activities (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Special emphasis is paid to task-based search, information retrieval, query processing and expansion, evaluation of returns' relevance, used information in a knowledge base, e-literacy and search skills, and sharing research information over the web (e.g. Arndt, 2010;Dickinson and Kim, 2002;Kani-Zabihi et al, 2006;Pomerantz et al, 2004;Spink, 2002;Vakkari, 2003). (4) The interoperability of the digital and networked libraries with the new paradigms of e-Science and e-learning has initiated a series of investigations on EL 30,6 the capability of the academic library to keep pace, and the librarians to engage with these activities (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The design of the system, as well as the terminology used, should be clear, consistent and easy to understand [15]. Moreover, there exists a preference for visual-based interfaces that support users in finding information [9]. In particular, map-based visualisations have demonstrated value [12].…”
Section: Background Literaturementioning
confidence: 99%
“…Key requirements for digital libraries that are consistently outlined in the literature are that the system should: (i) be easy to learn and easy to use; and (ii) deliver reliable search results [9,10]. The design of the system, as well as the terminology used, should be clear, consistent and easy to understand [15].…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Users usually input keywords to retrieve desired information but studies have showed that the retrieved results are not always what they expect [33]. Therefore, some tools like RSs have been developed to support users in information seeking and decision making [34].…”
Section: Rss In Digital Librariesmentioning
confidence: 99%